The dietetic treatment of a diabetic patient - Kerr, Almira E. (My University, 1908)
Introduction: In all medical treatment of the present day the fact is being realized that the health of a person depends upon the kind of food taken into the body. Let us consider what a food is. Food is anything which when taken into the body is capable either of building new tissue, repairing waste or producing heat or muscular work.
Citation: Kerr, Almira E. The dietetic treatment of a diabetic patient. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Food; Diabetes; Nutrition; Graduating theses; Senior theses; Theses